The effect of parents' employment on children's educational attainment - John Ermisch; Marco Francesconi (University of Essex, Institute for Social and Economic Research (ISER), 2000)
This paper presents the conditions under which a causal interpretation can be given to the association between childhood parental employment and subsequent education of children. In a model in which parental preferences are separable in own consumption and childrens well-being, estimation is complicated by endowment heterogeneity and by the fact that parents may compensate or reinforce childrens endowments relevant to education attainment. A sibling difference estimatation strategy is generally not sufficient to provide a consistent estimate of the parameter of interest. Identification rests on two stronger assumptions about the timing of parents knowledge of their childrens endowments and about the technology used to produce childrens human capital. We find a negative and signifcant effect on the childs educational attainment of the extent of mothers full-time employment when the child was aged 0-5. The effects of mothers part-time employment and fathers employment are smaller and less well determined but again negative. In the context of our conditional demand function framework, these results suggest that a higher full family income increases the educational attainment of children, and given full family income, a higher mothers or fathers wages reduces their childens educational attainment.
Keywords: 330